If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/2+3=X+6
We move all terms to the left:
X/2+3-(X+6)=0
We get rid of parentheses
X/2-X-6+3=0
We multiply all the terms by the denominator
X-X*2-6*2+3*2=0
We add all the numbers together, and all the variables
X-X*2-6=0
Wy multiply elements
X-2X-6=0
We add all the numbers together, and all the variables
-1X-6=0
We move all terms containing X to the left, all other terms to the right
-X=6
X=6/-1
X=-6
| 5p+7=-5+5p+6p | | 9+a/5=10 | | 4^3x/8^4x=2 | | 14-4m=42 | | 5n+7=3n-5 | | 11-13r=-17-15r | | 7/3x+14/3=8/3x+1 | | 5x+-4=6x+7 | | -19=v+6 | | 3(9x-2)^2+18x-4=x | | 38=-42+4w | | X(x–2)=x(x–1) | | -9(x-4)=11(3-x) | | 22+9f=49 | | -16.5m-15.98=2.4m+18.73+7.8 | | x+26.50=41.00 | | -5-2(n-4)=3(1+5n) | | 15=2t11 | | 20x-8=112 | | X+8=2x+22 | | -8n+-23=-79 | | 2x+2(x-6)=3x-6 | | 7(x+5)=-7(x+5 | | 15x+112=-68 | | 4r+6=2r-7 | | 7-2r=r-8 | | 12=y/8+3 | | 4/3=x/64 | | 18-7n=-52 | | r/7=9/7 | | 3/5q=1 | | 3w-8+3w=-2w+96 |